Primary Retroperitoneal Malignant Melanoma with Involvement of Iliac Artery and Vein. (6th September 2021) - Oulee, Aislyn; Xu, Ling; Worswick, Scott
Abstract : Primary retroperitoneal melanoma is a very rare extracutaneous presentation of melanoma. In this case report, we present a 65-year-old female with unilateral lower extremity edema secondary to occlusion of iliac vessels by a primary retroperitoneal melanoma tumor. We also review the findings in other cases previously described in the literature.